Dynamic L3 selves: a longitudinal study of five university L3 learners' motivational trajectories in China. Issue 2 (3rd March 2020) - Wang, Tianyi; Liu, Yongcan
ABSTRACT: The motivation to learn a third language (L3) has received increasing attention in research, especially with regard to how it evolves dynamically during the learning process. Underpinned by the L2 Motivational Self System [Dörnyei, Z. 2005. The Psychology of the Language Learner: Individual Differences in Second Language Acquisition . Mahwah, NJ: Lawrence Erlbaum], this paper reports on a longitudinal case study which explored learners' L3 motivational dynamics. It focused specifically on the developmental trajectories of these learners' ideal/ought-to L3 selves and the formation of such trajectories in relation to their language experiences. Three rounds of semi-structured interviews were conducted with five L3 learners of German at one Chinese university over two years. The data revealed that learners' L3 motivation fluctuated during the learning process. Whereas learners' ideal L3 selves displayed a clear upward trajectory in the first year and an observable decline at the later stage, their ought-to L3 selves became weaker in general over the two years. Moreover, learners' L3-related learning experiences were found to have contributed to the dynamics of their future L3 selves. Implications are discussed which point to the importance of assisting language learners to construct their ideal/ought-to selves and to increase their L3 motivation.